PP.18.25: DO GENETIC FACTORS INFLUENCE FEMORAL INTIMA-MEDIA THICKNESS? RESULTS FROM AN INTERNATIONAL TWINSTUDY. (June 2015) - Tarnoki, D.; Tarnoki, A.D.; Fejer, B.; Godor, E.; Molnar, A.A.; Kovacs, A.; Horvat, P. Maurovich; Medda, E.; Fagnani, C.; Stazi, M.A.; Merkely, B.; Farina, F.; et al.
Abstract : Objective: Increased femoral intima-media thickness (IMT) is considered a surrogate marker of cardiovascular disease and a prognostic factor of future cardiovascular events. Our aim was to assess the heritability of IMT of the common and superficial femoral arteries (CFA, SFA). Design and method: 161 Hungarian and Italian twin pairs from Padua, Perugia and Terni (83 monozygotic /MZ/, 78 dizygotic /DZ/; 135 men and 187 women, mean age 50 ± 13 years) underwent B-mode sonography of bilateral common and superficial femoral arteries (CFA, SFA). IMT was measured by Philips QLAB software. Heritability index was calculated based on the Falconer formula. Results: Significantly higher correlation was found in MZ compared to DZ pairs indicating a 62–100% and 11–63% rough heritability on CFA and SFA IMT bilaterally, respectively. Conclusions: Genetic factors seem to have a role in the determination of femoral IMT; however, the influence of environmental (lifestyle) factors still remains important. These preliminary findings support further collaborative initiatives to localize the specific genes and clarify the possible advantage of a family risk-based screening program.